Optimization of injection moulding parameters in reducing cavity pressure using Taguchi method - Md Ali, Mohd Amran; Mohd Ali, Noorfa Idayu; Md Fauadi, Muhammad Hafidz Fazli; Razak, Zakaria; K.J. Khadim (Penerbit Universiti Teknikal Malaysia Melaka, 2023)
This research focuses on optimization of injection moulding process parameters on cavity pressure that plays an important role not only limited to the quality of the moulded products but also for monitoring, optimizing and controlling the injection moulding process. The implementation of cavity pressure sensor can improve the product quality and reduce cost by eliminating waste. However, the parameters setting variation can increase the cavity pressure inside the mould during the injection moulding process that can affect the quality of plastic products. It is very important that the effect of injection moulding parameters on cavity pressure during the injection moulding process are to be determined. Therefore, the objective of this paper is to optimize the injection moulding parameters on cavity pressure using Taguchi method of polypropylene (PP). The selected parameters are temperature of mould (MoT), temperature of melt (MeT), time of injection (IT) and time of cooling (CT). The experiment is conducted using Taguchi method and analysis of variance (ANOVA) to determine the most significant parameter. During cavity pressure monitoring, the location of the pressure sensor installations is located near the gate and at the end of the cavity inside the mould. The experimental result shows that the optimal combination of injection machine parameters near the gate are MoT with 50°C, MeT with 310°C, IT with 0.7s and CT with 15.4 s. The similar set of optimum parameter setting for the cavity pressure at the end of the cavity is obtained except for MoT with 56°C. The improvement of reducing cavity pressure for both near the gate and end of the cavity is 1.18% and 1.30%, respectively. Thus, by using Taguchi optimization, the improvement of reducing cavity pressure can be achieved.